PASSAGE OF WHEAT FIRE IMPACT ON SOIL PROPERTIES AND ENVIRONMENT IN KURDISTAN REGION - & et al., Tariq (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2021)
The study was conducted to examine the effect of surface burn severity (Moderate, Severe and Unburned) of wheat straw on soil properties. The results showed statistical differences in some soil physical, chemical and biological properties. Bulk density and field capacity increased statistically by the severity of fire; however, porosity and infiltration rate were statistically lower in sever burned plot when compared to unburned plot. The chemical properties, soil organic matter (SOM), P, Ca, S, Cl, K, Mo, Fe and As were not affected by the fire. The pH value was increased slightly by increasing the fire severity, while, EC was decreased when compared with the unburned plot. It was found a statistical reduction in the number of bacterial and fungal cells per gram soil in the burned plots. A moderate and severe fire reduced seed germination percentage significantly. This finding suggests that fire severity may destruct the biological, physical and some of the chemical properties of the soil, and this may impact negatively on plant growth in the next growing season.